2004
DOI: 10.1016/j.tsf.2003.12.084
|View full text |Cite
|
Sign up to set email alerts
|

Bonding structure and hydrogen content in silicon nitride thin films deposited by the electron cyclotron resonance plasma method

Abstract: The bonding structure and hydrogen content of amorphous hydrogenated silicon nitride (a-SiN x :H) thin films have been investigated by infrared spectroscopy and ion beam techniques. Electron cyclotron resonance plasma enhanced chemical vapor deposition was used to produce these films under different values of gas flow ratio, deposition temperature, and microwave power.The amount of bonded hydrogen was calculated from the N-H and Si-H infrared absorption bands. An increase of the SiH 4 partial pressure during d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…It can be seen from the figure that the trends are clear, that the density of Si-H bonds decreases as the SiH 4 /N 2 flow ratio. This is in agreement with Martinez's results [15]. However, the density of N-H bonds follows the opposite trend.…”
Section: IIIsupporting
confidence: 93%
“…It can be seen from the figure that the trends are clear, that the density of Si-H bonds decreases as the SiH 4 /N 2 flow ratio. This is in agreement with Martinez's results [15]. However, the density of N-H bonds follows the opposite trend.…”
Section: IIIsupporting
confidence: 93%
“…USRN films with a thickness of 1.1 μm were deposited on a 50 μm thick SiO 2 substrate using inductively coupled chemical vapor deposition 6 at relatively low temperature of 250 °C. In the deposition, N 2 gas is used in replace of NH 3 for chemical reaction in forming Si 7 N 3 to minimize amount of H in the film because Si-H or N-H is a dominant absorption loss bonding at communication wavelength range of 1510–1565 nm 1115 . The material composition was previously characterized using FTIR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The process is exothermic with a favorable energy balance of 0.25 eV [23]. Also, it can be observed that the intensity of Si-N and Si-H stretching mode increases with increasing Si content of the film following the above reaction kinetics.…”
Section: Resultsmentioning
confidence: 99%